The Spiritual Meaning of the Liturgy : School of Prayer, Source of Life - Boselli, Goffredo (Book collections on Project MUSE., 2014)
"I am increasingly convinced that the decisive question that demands an answer from us is not so much how believers experience the liturgy, but whether believers live from the liturgy they celebrate." With these few words Goffredo Boselli captures the essence of this present work. Believers can celebrate the liturgy throughout their lifetimes without ever really drawing their lives from it. And this is true of all believers --laity, clergy, or monastics. More than a century after the start of the liturgical movement and half a century after the start of the postconciliar liturgical reform, we must ask the difficult question of whether the liturgy has or has not become the source of the spiritual life of believers. For only by living from the liturgy can they receive the nourishment necessary to maintain a life of faith in today's world. In The Spiritual Meaning of the Liturgy, Goffredo Boselli --one of Europe's foremost liturgical theologians -- offers an accessible and important guide for both scholars and interested laypeople to understand the meaning that permeates the liturgy and its implications for daily living. Readers will find here a resource to help understand the liturgy more fully, interiorize it more effectively, and live it more authentically. Goffredo Boselli is a monk of the community of Bose in Italy. He is a member of the organizing committee of the International Liturgical Congress held annually at Bose and serves as an advisor on the liturgy to the Italian Bishops Conference. He is also on the editorial board of the journals Rivista Liturgica and Arts Sacres. (Provided by publisher)